Students' Critical Thinking on Thermodynamics: Gender and Conceptual - Illahi, Beta Kurnia; Suwarma, Irma Rahma (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to analyze senior high school students' critical thinking skills in thermodynamics and explore gender-based differences in these skills. Methodology: A quantitative approach was employed with purposive sampling involving 132 students (34.1% male, 65.9% female) who had studied thermodynamics with the same teacher. Data were gathered using five essay questions designed to assess critical thinking components, including analysis, evaluation, inference, deduction, and induction. The collected data were analyzed to determine the level of critical thinking skills and potential differences between genders. Main Findings: The results showed that students’ critical thinking skills were generally low across all components: analysis (36.2%), evaluation (30.0%), inference (19.8%), deduction (28.3%), and induction (32.0%). While differences in critical thinking skills between male and female students were observed, they were not statistically significant. Novelty/Originality of this study: This study provides a detailed analysis of students' critical thinking skills in thermodynamics, highlighting specific weaknesses in key components. It offers a new perspective by examining gender-based differences in critical thinking, which are rarely explored in the context of physics education. The findings serve as a foundation for designing targeted educational strategies to address these deficiencies and improve critical thinking skills in science learning.